Effects of feeding organic and inorganic acid blends on growth performance and nutrient digestibility in young broiler chickens - Loh, Teck Chwen; Mohd Radzi, Rosyidah; Thanh, Nguyen Tien; Chang, Y. K.; Kok, P. C. (Veterinary Association Malaysia, 2007)
One hundred and ninety-six Ross chicks with an initial body weight of 40.30±0.22g were used to study the effects of different crude protein levels supplemented with dietry organic and inorganic acids on growth performance and nutrient digestibility. The chicks were caged in pens of seven animals each, and had ad libitum access to feed and water. The chicks were divided into 4 groups: Control -22% crude protein basal diet; T1:22% crude protein basal diet + Organics™; T2:20% crude protein basal diet + Organics™; T3:18% crude protein basal diet + Orgacids™. The apparent digestibility of crude protein, calcium and phosphorus was calculated using Ti02. The birds fed with Control, T1 and T2 had better growth performance and feed conversion ratio than T3. The diets added with acidifiers had better digestibility of crude protein, phosphorus and calcium. In conclusion, the chickens fed with Control, T1 and T2 had better weight gain than 18% CP with acid blends. However, similar growth performance was found between Control, T1 and T2. T1 and T2 had lower FCR than Control and T3. Better growth performance in Control, T1 and T2 is mainly attributed to the better digestibility of nutrients such as crude protein, phosphorus and calcium. There was a reduction of 17% SBM used in the diet when Control diet was compared with T2 diet.